1986
DOI: 10.1524/ract.1986.40.3.151
|View full text |Cite
|
Sign up to set email alerts
|

Third Phase Formation in the Extraction of Plutonium by Tri-n-Butyl Phosphate

Abstract: TBP, Plutonium/Third phase forrmtion llonic strength jn-dodecarte /Shellsol-T Summaiy Third phase formation in the extraction of plutonium(IV) by tri-n-butyl phosphate (TBP) in n-dodecane (DD) and Shellsol-T (SST) was studied. The effect of ionic strength on the limiting organic concentration (LOC) in Pu(N03)4 /30% TBP/DD system was studied and the LOC was found to increase nearly linearly with aqueous phase ionic strength. Data for the LOC of plutoniurndV) in 15% TBP/SST, 30% TBP/SST and 30% TBP/DD as a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Third phase formation with Pu(IV) is considered to be an important drawback when it comes to the reprocessing of fast reactor fuels, since the content of Pu in spent FBR fuel is much higher than that in spent LWR fuel. The third phase formation tendency of Pu(IV) by TBP increases in the presence of U(VI) [18]. In India, the spent fuel discharged from FBTR is being reprocessed in compact reprocessing of advanced fuels in Lead minicells (CORAL).…”
Section: Introductionmentioning
confidence: 99%
“…Third phase formation with Pu(IV) is considered to be an important drawback when it comes to the reprocessing of fast reactor fuels, since the content of Pu in spent FBR fuel is much higher than that in spent LWR fuel. The third phase formation tendency of Pu(IV) by TBP increases in the presence of U(VI) [18]. In India, the spent fuel discharged from FBTR is being reprocessed in compact reprocessing of advanced fuels in Lead minicells (CORAL).…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, a systematic study of the extraction of actinide ions by trialkyl phosphates has been initiated and detailed studies have been carried out on third phase formation in plutonium and thorium systems and U(VI)/Th(IV) Separation [9][10][11][12]. We have also reported earlier the results of a study on the effect of temperature on the extraction of uranium(VI) by TAP [13].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, it is clear that Pu(IV) will induce the formation of the third phase as does Th(IV). Additionally, the maximum total load in metallic cations for a 1 M TBP phase is estimated at about 0.5 M. It has also been shown that the behavior of third phase formation with Pu(IV) is not linear according to aqueous HNO 3 concentration, and much more sensitive to temperature than Th(IV) [ 11 , 28 ]. Thus, although process optimization will be needed, the temperature induced phase splitting is expecting to perform better in the presence of Pu(IV) than in the presence of Th(IV).…”
Section: Discussionmentioning
confidence: 99%